Niterói Operário: trabalhadores, política e lutas sociais na antiga capital fluminense (1942-1964) - Amaral, Luciana Pucu Wollmann do (2016)
This thesis aims to analyze the workers and urban workers (mainly manufacturing) from the city of Niterói, between the years 1942 and 1964. It is our interest here identify their forms of struggle, aspects of their union activity, market characteristics work which were inserted and the way in which these workers occupied the city and interacted with her. Having occupied the state capital office in Rio de Janeiro until the merger of the state with former Guanabara in 1975, Niterói just focusing on its territory a large number of local and state committees of political parties, and gather statewide unions and headquarters the federations of workers of different categories. Neighboring city of Rio de Janeiro, then federal capital, Niterói not only close to felt the 'heat' of the main political events taking place in the country at that time, but was also 'thermometer' of the struggles that were processed national scene in the pre-period 1964.